Post-Polypectomy Syndrome (PPS): A Case Report - Alshmandi, Mohamed; Butt, Haider Ali Tariq; Sheikh, Mahtab; Baghdadi, Khaled (Scripta Medica, 2026)
A 51-year-old female with unremarkable medical history developed right iliac fossa pain and fever one day post-polypectomy procedure. Management involved hospital admission for monitoring, supportive care with intravenous fluids and “nothing by mouth (NPO)”, broad-spectrum intravenous antibiotics and analgesia. The case here points the critical importance of post-polypectomy syndrome (PPS) occurring after cold endoscopic mucosal resection (EMR). Clinicians should consider PPS in patients admitted with fever, abdominal pain and raised inflammatory markers within a week of polypectomy, regardless of the technique used. Prompt CT imaging is crucial for accurate diagnosis and to exclude perforation.
Keywords: Colonoscopy; Endoscopic mucosal resection; Syndrome; Postoperative complications; Resection